PROMISES, PLANS AND PROGRAMMES OF D.M.K. (International Journal of Food and Nutritional Sciences, 2022)
Tamil traditionalism, the absence of the idea of idolatry in the Party, broad mass contact, attachment and allegiance of the Party's rank and file, the lack of groupism or factionalism of any kind, the administrative structure of the Party, and the easily understood and practical programmes all served as the foundation for the Party to democratically plan its policies while the Party received public opinion, forming the go In developing its programmes, the D.M.K. benefited from its practical experience as an opposition party from 1957 to 1967. The leadership's ability to formulate policies that suited the requirements of the general populace was greatly aided by the bond that existed between the Party and the general population. the caste-focused. Because D.M.K. never gave casteism or communalism any weight and because of its wide viewpoint, it was able to develop policies that were acceptable to the majority of Tamil society.3 Even though that party did not hold the reins of power between February 1976 and January 1989, the fact that it managed to win a resounding majority in January 1989 despite displacing a major national party like the Congress is evidence that its policies and programmes had a broad enough appeal to appeal to all demographic groups.